BACILLUS SP RM3 ISOLATED FROM MANGROVE FOREST HAS POTENTIAL AS ANTIBACTERIAL ACTIVITY AND CYTOTOXICITY - Maheswari, Ida Ayu Kartika; Indraningrat, Anak Agung Gede; Paramasatiari, Anak Agung Ayu Lila; Choe, Daegeun (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2025)
Background: Antibacterial resistance is a critical health concern, driving the search for new compounds from natural sources such as mangrove-associated bacteria, which produce diverse secondary metabolites.Objective: This research focused on studying the bioactivity of the extract of Bacillus sp. RM3, previously isolated from mangrove forests through an extraction method using ethyl acetate solvent.Methods: The Bacillus sp. RM3 isolate was fermented in ISP-2 media and extracted with ethyl acetate. The resulting crude extract was tested for antibacterial activity using the Kirby-Bauer method against Staphylococcus aureus ATCC 25923, Streptococcus mutans FNCC 0405 (Gram-positive), Escherichia coli ATCC 25922, and Klebsiella pneumoniae ATCC 700603 (Gram-negative). Cytotoxic effects were assessed via the Brine Shrimp Lethality Assay (BSLT).Results: The ethyl acetate extract displayed moderate antibacterial activity, evidenced by inhibition zone diameters between 5 to 10 mm. Triplicate measurements revealed the following average inhibition zone diameters: E. coli (9.65±1.62 mm), K. pneumoniae (7.88±1.92 mm), S. aureus (7.77±1.26 mm), and S. mutans (7.03±0.99 mm). Furthermore, the BSLT assay revealed an LC50 value of 504.586 ppm, which indicates the extract was toxic (LC50 1000 ppm).Conclusions: Overall, these results indicate the potential of Bacillus sp. RM3 isolate as a producer of antibacterial and cytotoxic compounds